The Effectiveness of Legal Policies on Micro and Small Business Empowerment in Pandemic Time - Ilyas, Muhammad; Ramadani, Rizki (SASI, 2022)
Introduction: MSMEs made a significant contribution to the Indonesian economy at the beginning of 2018. However, since COVID-19 has become a global pandemic, micro, small, and medium-sized enterprises (MSMEs) have been heavily impacted, due to a series of social restriction policies enacted by the government. In order to resolve issues, the government must assist and empower the MSME sector so that it can survive the pandemic. However, not many studies have been carried out regarding the extent to which empowerment policies by local governments have been effective in the field. Purposes of the Research: This study aims to determine the effectiveness of the legal policies in empowering the micro and small enterprises (MSEs) during the pandemic based on the case of Gowa Regency, South Sulawesi.Methods of the Research: This is an empirical normative legal research that uses primary and secondary data with descriptive and qualitative analysis.Results of the Research: The results show that the empowerment policy in South Sulawesi has been regulated in Provincial Regulation Number 7 of 2019 concerning Cooperatives and Small Enterprises, where there are ten forms of facilitating MSE empowerment. Even though it has established the Cooperatives and MSMEs Office, the Gowa Regency Government does not yet issue spesific regulations on the empowerment of MSEs. Based on field data analysis, it was found that several forms of empowerment facilitation had been received by the respondents but were not evenly distributed. Empowerment received mostly focused on capital facilitation, while ignoring other form of facilitations. Thus, the existing policies have not been implemented effectively. This is influenced by several factors such as legal substance that do not provide legal certainty; legal structure factors, including the lack of apparatus and supporting facilities; and cultural factors, such as pragmatic behavior and low awareness of MSE actors.